2023
DOI: 10.1109/tii.2022.3203059
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Influential Nodes for Smart Enterprises Using Community Structure With Integrated Feature Ranking

Abstract: Finding influential nodes reshuffles the very notion of linear paths in business processes and replaces it with networks of business value within a smart enterprise system. There are many existing algorithms for identifying influential nodes with certain limitations for applying in large-scale networks. In this paper, we propose a community structure with an Integrated Features Ranking (CIFR) algorithm to find influential nodes in the network. Firstly, we use the community detection algorithm to find communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…14 The explanation for this is that these measurements ignore edge weights, which might contain important information about the significance of nodes and the potency of their connections. 15,16 Additionally, conventional centrality measurements frequently presume that all edges are equally essential, which may be false. Various methods have been proposed to address these limitations, incorporating edge weights in centrality measures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The explanation for this is that these measurements ignore edge weights, which might contain important information about the significance of nodes and the potency of their connections. 15,16 Additionally, conventional centrality measurements frequently presume that all edges are equally essential, which may be false. Various methods have been proposed to address these limitations, incorporating edge weights in centrality measures.…”
Section: Introductionmentioning
confidence: 99%
“…Still, recent research has indicated that they might not be adequate for correctly identifying prominent nodes 14 . The explanation for this is that these measurements ignore edge weights, which might contain important information about the significance of nodes and the potency of their connections 15,16 . Additionally, conventional centrality measurements frequently presume that all edges are equally essential, which may be false.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the influence of community structure on node centrality in complex networks has gained extensive attention from researchers. Kumar et al [23] proposed a community structure algorithm called CIFR which integrates feature ordering to detect influential nodes using the characteristics of community propagation in the network. Sun et al [24] introduced a new community-based K-shell decomposition algorithm called CKS.…”
Section: Introductionmentioning
confidence: 99%
“…An essential technique for social network analysis is community discovery, which will be created to find groups of nodes that share characteristics. In particular, community detection is a crucial component of network analysis that has been used in numerous practical applications, such as fraud detection, community detection, recommendation systems, influential node detection, and link prediction, among others [1][2][3][4]. Common community detection methods look for strong intracommunity and low inter-community similarity, which indicates that nodes inside a community have high pairwise similarity scores while nodes in nearby communities have low pairwise similarity scores, to locate node clusters [5].…”
Section: Introductionmentioning
confidence: 99%